Oligomycins inhibit Magnaporthe oryzae Triticum and suppress wheat blast disease. - Moutoshi Chakraborty; Nur Uddin Mahmud; Abu Naim Md Muzahid; S M Fajle Rabby; Tofazzal Islam (PLoS ONE, 2020)
Oligomycins are macrolide antibiotics, produced by Streptomyces spp. that show antagonistic effects against several microorganisms such as bacteria, fungi, nematodes and the oomycete Plasmopara viticola. Conidiogenesis, germination of conidia and formation of appressoria are determining factors pertaining to pathogenicity and successful diseases cycles of filamentous fungal phytopathogens. The goal of this research was to evaluate the in vitro suppressive effects of two oligomycins, oligomycin B and F along with a commercial fungicide Nativo® 75WG on hyphal growth, conidiogenesis, conidial germination, and appressorial formation of the wheat blast fungus, Magnaporthe oryzae Triticum (MoT) pathotype. We also determined the efficacy of these two oligomycins and the fungicide product in vivo in suppressing wheat blast with a detached leaf assay. Both oligomycins suppressed the growth of MoT mycelium in a dose dependent manner. Between the two natural products, oligomycin F provided higher inhibition of MoT hyphal growth compared to oligomycin B with a minimum inhibitory concentration of 0.005 and 0.05 μg/disk, respectively. The application of the compounds completely halted conidial formation of the MoT mycelium in agar medium. Further bioassays showed that these compounds significantly inhibited MoT conidia germination and induced lysis. The compounds also caused abnormal germ tube formation and suppressed appressorial formation of germinated spores. Interestingly, the application of these macrolides significantly inhibited wheat blast on detached leaves of wheat. This is the first report on the inhibition of mycelial growth, conidiogenesis, germination of conidia, deleterious morphological changes in germinated conidia, and suppression of blast disease of wheat by oligomycins from Streptomyces spp. Further study is needed to unravel the precise mode of action of these natural compounds and consider them as biopesticides for controlling wheat blast.